The Reality of Management of Professional Training Activities for Teachers at Preschools in an Giang Province, Vietnam Country - Thang, Nguyen Bach (International Journal of Membrane Science and Technology, 2023)
Author has conducted a survey on the management of professional development activities for preschool teachers in An Giang province. The survey results show the strengths, limitations and causes of the management of professional development activities for preschool teachers in An Giang province in the past times. Thereby, it is the basis for leaders to research measures to foster professional skills for preschool teachers in An Giang province to meet the requirements of improving teaching quality in preschools of An Giang province.